### Need help from an expert?

The world’s top online tutoring provider trusted by students, parents, and schools globally.

The integral of ln(x) is xln(x) - x + C, where C is the constant of integration.

To find the integral of ln(x), we use integration by parts. Let u = ln(x) and dv = dx. Then du/dx = 1/x and v = x. Using the formula for integration by parts, we have:

∫ln(x) dx = xln(x) - ∫x(1/x) dx

= xln(x) - ∫dx

= xln(x) - x + C

where C is the constant of integration.

We can check our answer by differentiating it using the product rule. Let y = xln(x) - x + C. Then

dy/dx = d/dx(xln(x)) - d/dx(x) + d/dx(C)

= (x d/dx(ln(x)) + ln(x)) - 1 + 0

= ln(x) + 1/x - 1

= ln(x)/x

which is the integrand we started with, so our answer is correct.

Note that the integral of ln(x) is only defined for x > 0, since ln(x) is not defined for x ≤ 0.

Study and Practice for Free

Trusted by 100,000+ Students Worldwide

Achieve Top Grades in your Exams with our Free Resources.

Practice Questions, Study Notes, and Past Exam Papers for all Subjects!

The world’s top online tutoring provider trusted by students, parents, and schools globally.

Loading...

Loading...